Dampak Penggunaan Media Pengajaran Interaktif dalam Meningkatkan Motivasi dan Hasil Belajar Siswa di Sekolah Dasar - Ika Rusnia; Ari Suriani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Examining how elementary school students' motivation and academic performance are affected by the use of interactive learning tools is the primary goal of this study. One of the developments that might pique students' interest in learning and get them more involved in the process is interactive learning media, which presents information in a more engaging and accessible way. Study was conducted using a quantitative approach using a quasi-experimental design. Students in fifth grade from one of the local elementary schools served as the study sample. They were split into two groups, one for the experiment and one for control. While the control group stuck to more traditional approaches, the experimental group made use of interactive learning materials. Testing for reliability and validity was not conducted on the learning motivation questionnaire and learning accomplishment assessments that were used to gather data. To compare the groups' levels of motivation and academic success, a t-statistical test was used to analyze the data. Using interactive learning media significantly increased students' learning motivation compared to the control group, according to the findings. Furthermore, compared to the group that relied on conventional methods of instruction, students in the test group outperformed them academically. These findings show that elementary school students may be motivated and accomplish more with the use of interactive learning tools. In order to make learning more engaging and conducive to student achievement, instructors are encouraged to include interactive media into the learning process